Alveolar crystal burden in stone workers with artificial stone silicosis. Issue 6 (17th February 2022) - Apte, Simon H.; Tan, Maxine E.; Lutzky, Viviana P.; De Silva, Tharushi A.; Fiene, Andreas; Hundloe, Justin; Deller, David; Sullivan, Clair; Bell, Peter T.; Chambers, Daniel C.
Abstract: Background and objective: An epidemic of silicosis has emerged due to a failure to control risks associated with exposure to high‐silica content respirable dust generated while working with artificial stone products. Methods for quantification of alveolar crystal burden are needed to advance our understanding of the pathobiology of silica‐related lung injury as well as assisting in the diagnosis, clinical management and prognostication of affected workers. The objective of this study was to develop and validate novel methods to quantify alveolar crystal burden in bronchoalveolar lavage (BAL) fluid from patients with artificial stone silicosis. Methods: New methods to quantify and analyse alveolar crystal in BAL from patients with artificial stone silicosis were developed. Crystals were isolated and counted by microscopy and alveolar crystal burden was calculated using a standard curve generated by titration of respirable α‐Quartz. The utility of the assay was then assessed in 23 patients with artificial stone silicosis. Results: Alveolar crystal burden was greater in patients with silicosis (0.44 picograms [pg]/cell [0.08–3.49]) compared to patients with other respiratory diagnoses (0.057 pg/cell [0.01–0.34]; p < 0.001). Alveolar crystal burden was positively correlated with years of silica exposure (ρ = 0.49, p = 0.02) and with decline in diffusing capacity of the lungs for carbon monoxide (ρ = −0.50, p = 0.02). Conclusion: Alveolar crystal burden quantification differentiates patients with silicosis from patients with other respiratory disorders. Furthermore, crystal burden is correlated with the rate of decline in lung function in patients with artificial stone silicosis. Abstract : In this study, we develop and validate an assay to quantify alveolar crystal burden in bronchoalveolar lavage fluid from patients with artificial stone silicosis. This assay may be a useful adjunct in the diagnosis of silicosis and assessing response to therapeutic intervention. See related Editorial